The empirical relationship between average asset correlation, firm probability of default, and asset size - Lopez, Jose A. (Journal of Financial Intermediation, 2004)
The asymptotic single risk factor approach is a framework for determining regulatory capital charges for credit risk, and it has become an integral part of the second Basel Accord. Within this approach, a key parameter is the average asset correlation. We examine the empirical relationship between this parameter, firm probability of default and firm asset size measured by the book value of assets. Using data from year-end 2000, credit portfolios consisting of US, Japanese, and European firms are analyzed. The empirical results suggest that average asset correlation is a decreasing function of probability of default and an increasing function of asset size. The results suggest that these factors may need to be accounted for in the final calculation of regulatory capital requirements for credit risk.